Monetary Policy in the Presence of Supply Constraints: Evidence from German Firm-Level Data - Almut Balleer; Marvin Noeller (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using firm-level survey data from Germany, this paper asks how do supply constraints propagate monetary policy shocks? To answer this question, we first offer a general discussion on the measurement of supply constraints. We show that capacity utilization, a widely accepted measure of bottlenecks and slack, is only an imperfect measure for supply constraints as a whole. Consequently, we distinguish between input and capacity constraints and show that this distinction is crucial to understand the propagation of monetary policy in the presence of supply constraints: the probability to increase prices rises sharply for input constraint firms in response to an expansionary monetary policy shock, independent of their level of capacity utilization. This result challenges a recent literature that argues that capacity utilization is a sufficient statistic to understand the propagation of aggregate shocks in the presence of production limitations.
Keywords: E31; E52; C22; 330; supply constraints; capacity utilization; price setting; local projections; monetary policy